Sengketa Laut Cina Selatan: Analisis Realis terhadap Perebutan Kekuasaan, Respon Regional, dan Implikasi Geopolitik - Agus Rohmat Hidayat; Nur Alifah; Agis Ahmad Rodiansjah; Muhammad Zaenal Asikin (Jurnal Syntax Admiration, 2024)
The South China Sea dispute has emerged as a complex and highly contentious issue with significant implications for regional stability. From a realist perspective, these disputes reflect power struggles and influence among claimant states, driven by their desire to secure strategic interests in the region. Neighboring countries, recognizing the impact of China's rise as a great power, have responded by boosting their military capabilities and forming alliances to counterbalance China's growing influence. However, analyzing South China Sea disputes through a realist lens provides valuable insights into power struggles, vested interests, and security issues underlying the conflict. Through a critical review of territorial claims, legal frameworks, and the historical context of disputes, this paper provides a comprehensive understanding of the multifaceted nature of such disputes. In addition, the report explores the geopolitical implications and involvement of major powers in the region.